Statistical analysis of the temporal single-photon response of superconducting nanowire single photon detection - 何宇昊 吕超林 张伟君 张露 巫君杰 陈思井 尤立星 王镇 (Chinese physics B, 2015)
A new method to study the transient detection efficiency （DE） and pulse amplitude of superconducting nanowire single photon detectors （SNSPD） during the current recovery process is proposed -- statistically analyzing the single photon response under photon illumination with a high repetition rate. The transient DE results match well with the DEs deduced from the static current dependence of DE combined with the waveform of a single-photon detection event. This proves that static measurement results can be used to analyze the transient current recovery process after a detection event. The results are relevant for understanding the current recovery process of SNSPDs after a detection event and for determining the counting rate of SNSPDs.